THE IMPACT OF NEW AGE MUSIC AS TREATMENT TO REDUCE STRESS - Henny Regina Salve (Universitas Gunadarma, 2007)
New Age music is the same as Alternative music. The term New Age take various forms and directions. This music draws on some of the flow of the music on this list, temasuk Ambient, Minimalism, Native American, Drum and Percussion, World, Electronic, Celtic, and Alternative. In music also use this technique entrainment and binaural beats. Entrainment is a principle in physics and is defined as the synchronization of two or more rounds rhythm (synchronization of two or more cycles rhytmic). The principle of this special can be used to create a resonance or synchronization in the brain of a specific frequency. While binaural beats found in 1939 by German eksperimenter HW Dowe. Human ability to